What Are The Comparative Mortality Rates, Healthcare Costs, And Patient-Reported Quality Of Life Outcomes For End-Stage Renal Disease Patients Undergoing Dialysis Versus Kidney Transplantation? - Kadek Cahya Adwitya; Arinda Rindang Nastietie; I Gede Yasa Arga Winangun; Anastasya Savira; Putu Bagus Wisnu Mahadiputra; Putu Rico Aditya Pangestu (International Medical Journal Corp. Ltd, 2025)
Introduction: End-stage renal disease (ESRD) requires renal replacement therapy (RRT) to sustain life, primarily through dialysis or kidney transplantation. Treatment choice significantly affects mortality, quality of life, and healthcare costs. Methods: This report synthesizes findings from multiple comparative studies, including retrospective cohorts, prospective cohorts, and randomized controlled trials, evaluating outcomes of dialysis (hemodialysis and peritoneal dialysis) versus kidney transplantation. Outcomes assessed include mortality rates, quality of life measures, psychological impacts, and healthcare resource utilization. Results: Mortality rates were consistently lower in kidney transplant recipients compared to dialysis patients, with transplantation showing survival rates up to 91% at 10 years versus 40.9% for hemodialysis and 22.8% for peritoneal dialysis. Quality of life and psychological well-being were significantly better in transplant patients, with improvements in sexual function, reduced anxiety and depression, and enhanced social support. Healthcare costs varied, with some evidence suggesting higher monthly expenditures for dialysis, particularly continuous ambulatory peritoneal dialysis. Exercise interventions improved physical function in both groups. Discussion: Kidney transplantation offers superior survival and quality of life benefits but is limited by donor availability and patient eligibility. Dialysis remains essential for many patients but is associated with higher mortality and psychological burden. Shared decision-making and patient education are critical to optimize treatment selection. Conclusion: Kidney transplantation is the preferred treatment for eligible ESRD patients due to better survival and quality of life outcomes. Further research is needed to improve dialysis modalities and address cost-effectiveness.